An integrated geophysical study of Kraseaw Dam, Thailand - NARONGCHAI WIWATTANACHANG (International Association of Lowland Technology, 2021)
The study was conducted using seismic reflection and electrical resistivity methods including several techniques such as electrical resistivity imaging, seismic refraction and seismic reflection to determine the stability of the dam. The survey used a case study of Krasiao-Dam in Dan-Chang district Suphan-Buri Thailand. Krasiao-Dam is valid for a period of several years, suiting our study. The electrical resistivity data was processed and presented as 2D underground cross section. An integrated data analysis of these two results were verified of possible leakage position or risk location as it needed to be tested by conventional engineering testing methods. Seismic survey results indicate that the dam layers structure; which included compaction soil, is shown with the wave speed as between 400-900 m/sec, ground improved layer and bed rock has a higher signal speed of 1,000 m/sec.